Improving Student’s Speaking Skill Using Duolingo Application at SDN 74/II Tanah Periuk - Namira Putri Lia Haliza; Levandra Balti; Renda Lestari (Master Journal of Future Education, 2025)
This study aims to improve the speaking skills of fifth grade students at SDN 74/II Tanah Periuk by using the Duolingo application as a learning medium and this study aims to determine whether using the Duolingo application can improve students speaking skills and to describe the process of improvement during teaching and learning activities. This study also aims to provide an alternative learning medium that is effective, engaging, and able to motivate students to practice speaking English interactively. This research employed Classroom Action Research (CAR) with 26 fifth-grade students at SDN 74/II Tanah Periuk as subjects. The study was conducted in two cycles, each consisting of two meetings. The data collection instruments were teacher observation sheets, student observation sheets, and tests. The research was conducted in the second semester of the 2025/2026 acedemic year. Based on the results of data analysis, it is know that after the Duolingo application was implemented the learning process and students’ speaking skills experienced a significant increase. This is demonstrated by the results of teacher teaching observations in cycle I, which increased by 70% in cycle II to 88%. Furthermore, the average students learning process increased in cycle I to 59,61% (Satisfactory) and increased to 84,61% in cycle II. Similarly, the percentage of student learning achievement in cycle I increased from 69,23% to 88,46% in cycle II. Therefore, the implementation of the Duolingo application can improve the learning process and outcomes of fifth-grade students at SDN 74/II Tanah Periuk in English